Rekontruksi Asas Tabellionis Officium Fideliter Exercebo Dalam Perspektif Cyber Notary: Studi Perbandingan Indonesia dan Amerika Serikat - Aulia, Farah Nizrina; Ali, Moh.; Sari, Nuzulia Kumala (Acten Journal Law Review, 2025)
Cyber ​​notary as part of the development of digital technology has become a new innovation in notary services. However, in the midst of the presence of cyber notary, it raises new challenges, especially in the aspect of the classical principles of notary, especially the principle of Tabellionis Officium Fideliter Exercebo which is oriented towards the notary's devotion to the duties that have been carried out so far. This article is oriented to examine the concept of cyber notary and the principle of Tabellionis Officium Fideliter Exercebo in terms of challenges and implementation. In addition, this article contains a comparative study of other countries using the United States as a reference for comparison as well as a representative of the use of cyber notary. This research is a legal research that uses a statutory approach and a comparative approach to describe ideas for the renewal of notary law in the aspect of cyber notary in Indonesia. The result of this research show The concept of cyber notary has shifted the paradigm of conventional notaries based on physical to digital systems. However, in its implementation, it does face quite big challenges. A comparative study with the United States through the RON system shows that this country has succeeded in adjusting notary integrity with job accountability through legal means and infrastructure, as well as forming national standards that represent technological progress without sacrificing ethical aspects. Therefore, there needs to be a rigid regulation in the Notary Law that represents progressive positive law in responding to the challenges of the development of the era, by reformulating notary law that not only accommodates technological devices, but also reconstructs the meaning of job fidelity in aspects that are in accordance with the values ​​of trust and caution.